Penerapan pendekatan PMRI (pendidikan matematika realistik indonesia) untuk meningkatkan aktivitas dan hasil belajar matematika pada materi keliling dan luas persegi panjang siswa kelas III MIN 8 Aceh Barat Daya - Narwati, Narwati (Universitas Serambi Mekkah, 2020)
The purpose of this study is to improve the activities and learning outcomes of mathematics on the mate-rial and rectangular area of class III MIN 8 students in Southwest Aceh. The learning model used in this study is PMRI (Indonesian Realistic Mathematics Learning). The subjects of this study were students in grade III MIN 8 Southwest Aceh. The number of students is 25 students with 15 male students and 10 female students. This research was conducted in the 2017/2018 school year within a period of 3 months, from February 2018 to April 2018 in the even semester. The methodology of this research is Classroom Action Research (CAR) consists of two cycles and each cycle consists of two meetings. Each cycle con-sists of planning, implementing, observing and reflecting. Data collection technique is to collect the val-ue of the test carried out at the end of each learning in each cycle using the question instrument (written test). Observation data is done by looking at the activeness of students in the learning process. Data were analyzed by means of percentage statistics. The results showed that there was an increase in stu-dent learning activities in both cycles, from the category of being good enough and the good category increasing to very good. Completeness of student learning outcomes has increased from 44% in the pre cycle increased to 64% in the first cycle and increased to 80.77% in the second cycle. The use of the PMRI model can improve mathematics learning activities and outcomes on the perimeter and rectangular area of third grade students MIN 8 Aceh Barat Daya 2017/2018 Academic Year.